NILAI RELASIONAL MODEL KALIMAT DALAM WACANA KAMPANYE CALON GUBERNUR DAN WAKIL GUBERNUR SULAWESI SELATAN PERIODE 2008 – 2013 (ANALISIS WACANA KRITIS) Relational Value of Sentences Models in Campaign Discourse of Governor and Vice Governor Candidates of South Sulawesi in the Period of 2008—2013) - Armiati Rasyid (SAWERIGADING, 2009)
The objectives of the research are to describe, to interpret, and to explain the use of the relational value of sentences models in Campaign Discourse of Governor and Vice Governor Candidates of South Sulawesi in the Period of 2008—2013. The method used qualitative approach. It is a kind of critical discourse analysis of Fairclough Model that analyzes on three dimensions of discourse started from the text description to the interpretation and explanation. Result of the study shows that the three candidates have used the efficiency of the value in sentences models includes the use of declarative model, interogative model, and imperative model.All of the sentences models are used to assert the candidate identity, to show program, and to engrave the ideology values suchas religious value, local cultural value, and grammatical value. Those are the opponent which cover the partisan and non-partisan of the candidates, among the candidates, even toward the certain institution.